The great Mrs. Elias : [large type] a novel based on a true story - Chase-Riboud, Barbara (Thorndike Press Large Print Historical fiction, 2022)
"The author of the award-winning Sally Hemings now brings to life Hannah Elias, one of the richest black women in America in the early 1900s, in this mesmerizing novel swirling with atmosphere and steeped in history. A murder and a case of mistaken identity brings the police to Hannah Elias' glitzy, five-story, twenty-room mansion on Central Park West. This is the beginning of an odyssey that moves back and forth in time and reveals the dangerous secrets of a mysterious woman, the fortune she built, and her precipitous fall. Born in Philadelphia in the late 1800s, Hannah Elias has done things she's not proud of to survive. Shedding her past, Hannah slips on a new identity before relocating to New York City to become as rich as a robber baron. Hannah quietly invests in the stock market, growing her fortune with the help of businessmen. As the money pours in, Hannah hides her millions across 29 banks. Finally attaining the life she's always dreamed, she buys a mansion on the Upper West Side and decorates it in gold and first-rate décor, inspired by her idol Cleopatra. The unsolved murder turns Hannah's world upside-down and threatens to destroy everything she's built. When the truth of her identity is uncovered, thousands of protestors gather in front of her stately home. Hounded by the salacious press, the very private Mrs. Elias finds herself alone, ensnared in a scandalous trial, and accused of stealing her fortune from whites. Packed with glamour, suspense, and drama, populated with real-life luminaries from the period, The Great Mrs. Elias brings a fascinating woman and the age she embodied to glorious, tragic life"--